Treatment of high fat diet‐induced obese pregnant mice with IL‐6 receptor antibody does not ameliorate placental function and fetal growth restriction. (22nd May 2022) - Kretschmer, Tobias; Turnwald, Eva‐Maria; Janoschek, Ruth; Wohlfarth, Maria; Handwerk, Marion; Dötsch, Jörg; Hucklenbruch‐Rother, Eva; Appel, Sarah
Abstract: Problem: : Pregnancy complications and adverse birth outcomes are in part fueled by the rise in obesity and its associated co‐morbidities in western societies. Fetal healthy development and placental function are disturbed by an obese, inflammatory environment associated with cytokines, such as interleukin‐6, causing inadequate supply of nutrients to the fetus and perinatal programming with severe health consequences. Method of Study: : Mice received high fat diet (HFD) before and during gestation to induce obesity. We performed an IL‐6 receptor antibody (MR16‐1) treatment in pregnant obese mice at embryonic days E0.5, E7.5 and E14.5 to investigate whether this could ameliorate HFD‐induced and obesity‐associated placental dysfunction, evaluated by stereology and western blot, and improve offspring outcome at E15.5 in obese dams. Results: : We observed fewer fetuses below the 10th percentile and placental vascularization was less aggravated following MR16‐1 treatment of obese dams, showing slight improvements in labyrinth zone (Lz) vascularization. However, placental dysfunction and fetal growth restriction were still apparent in MR16‐1 dams compared to lean control dams. Molecular analysis showed significantly elevated IL‐6 level in placentas of MR16‐1 treated dams. Conclusion: : Treatment with MR16‐1 blocks IL‐6 signaling in the placenta, but has only limited effects on preventing HFD‐associated placental dysfunction and offspring outcomes in mice, suggesting further mechanisms in the deterioration of placental vascularization and fetal nutrient supply as a consequence of maternal obesity.